Analysis of Sunshine Temperature Field of Steel Box Girder Based on Monitoring Data - Hailin Lu; Jing Hao; Jiwei Zhong; Yafei Wang; Hongyin Yang (Advances in Civil Engineering)
In this study, based on the recorded meteorological data of the bridge site, a spatial-temporal temperature model of a 3-span steel box girder is developed through applying the thermal analysis software TAITHERM. Firstly, the rationality and dependability of the proposed spatial-temporal temperature model are adequately verified by means of implementing the comparison with the measurement data. Then the temperature distribution of the steel box girder is analyzed and discussed in detail. The analytical results show that the time of the bottom of pavement reaching the daily maximum temperature lags behind the top of pavement by 2 or 3 hours due to the thermal insulation effect of pavement, and the maximum vertical temperature gradient of the structure exceeds the existing standards. Moreover, with the help of the analytical model, a parametric study of comprehensively meteorological factors is also performed. The results of the sensitivity analysis indicate that solar radiation is the most significant factor affecting the maximum vertical temperature gradient of the steel box girder, followed by air temperature and wind speed. After that, with the representative values of the extreme meteorological parameters during 100-year return period in Wuhan City in China being considered as the thermal boundary conditions, the temperature distribution of the steel box girder is further studied for investigation purpose. The results demonstrate that the heat conduction process of the steel box girder has distinct “box-room effect,” and it is of great necessity to consider both the actual weather conditions at the bridge site and the “box-room effect” of steel box girder when calculating thermal behaviors of bridge structures. Finally, it is related that the particular method proposed in this paper possesses a satisfactory application prospect for temperature field analysis upon various types of bridges in different regions.